23 Gauge Lens Sparing Vitrectomy For Stage 4 ROP In Lasered Eyes - Balbir Khan; Vartika Anand; Bhavna Sobat Trikha (Delhi Journal of Ophthalmology)
Purpose: To assess the visual and anatomical outcomes after primary lens-sparing pars plana vitrectomy for Stage 4 ROP in lasered eyes. Materials and Methods: In this retrospective, interventional, consecutive case series, the records of 20 eyes of 10 patients were taken, of which 5 eyes had stage 5 ROP and closed funnel RD, and hence were left alone. The remaining 15 eyes that had stage 4 ROP with RD, underwent primary 3 port lens sparing vitrectomy. The outcomes studied at the final follow-up visit were the retinal status, lens and media clarity and visual acuity. Favorable anatomical outcome was defined as the retinal reattachment of the posterior pole at two months, regression of knife edge like fold after the surgery and no dragging of disc or macula.; and favorable functional outcome was defined as a central, steady and maintained fixation, with the child following light. Results: At mean follow-up of 6 months, the lens remained clear in all the eyes, and the media clarity was maintained in all cases. A total of 13 eyes had favourable anatomical and functional outcome. Intraoperative complications included vitreous Hemorrhage and iatrogenic break formation. No preop or intraoperatively anti-VEGF agent was used except in one eye. Conclusion: 23 G Lens-sparing vitrectomy helps to achieve a favorable anatomical and functional outcome in selected cases of Stage 4 ROP with lasered eyes.